Video documental sobre la memoria histórica de diez iglesias representativas del centro hitórico de Quito - Palacios Osorio, Wendy del Carmen (2015)
The present investigation work, has been divided in three chapters and documentary video In chapter one takes as reference the most relevant for this research theoretical livelihoods, moving from the theoretical to the conceptual, expressing the view that has been taken as a reference for the work, the most representative premises that have served as support for the assumptions made before the documentary, are resolved in this instance that CITES authors of various philosophical currents and is prescribed with the regulations and laws of “El Plan Nacional del Buen Vivir 2013- 2017” and the Constitution of the Republic of the Ecuador. Chapter two is the result of field research conducted in ten churches of the historic centre of the city of Quito, will review data architectural, artistic, political, anecdotal, religious, economic and symbolic of the planning, construction and l'arranjament of each. The information is the product of interviews with historians, priests and guides tourist of each temple, as well as a compilation collection of historical texts that priests priests put at my disposal. Chapter three relates in detail the construction of the documentary video, demonstrating the processes that were carried out and the resources used. The literary script and the technical script with the cornerstone of the chapter since they present, in the form of sketch the final product. Finally, the fourth part of this thesis is the presentation of documentary video as a DVD product that lasts nine minutes. The documentary addresses the subjectivity of the author, who performs the narration voice-over, to relate their own vision of the events after the process of conquest and colonization of these lands Quito carried out by those who gave the name of this city as "San Francisco de Quito".